2012
DOI: 10.3126/nje.v2i1.6378
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Asthma in School Going Children in South India

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…In the present study, the prevalence of asthma in Meerut city was found to be 11.03 percent. The findings of this study are consistent with several other studies conducted elsewhere [5][6][7][8] . However, Zaman et al 9 reported a much higher prevalence rate of 16.1% amongst Bangladeshi school children.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the prevalence of asthma in Meerut city was found to be 11.03 percent. The findings of this study are consistent with several other studies conducted elsewhere [5][6][7][8] . However, Zaman et al 9 reported a much higher prevalence rate of 16.1% amongst Bangladeshi school children.…”
Section: Resultssupporting
confidence: 93%
“…The cut-off point ranges for birthweight categories were: 2.0–3.2, 2.1–3.2 and 3.5–4.5 kg, for the ‘Low’, ‘Normal’, and ‘High’ birthweight categories, respectively 23 24 52–59. One other study used 2.7 kg as a cut-off point 60. The variation in the cut-off points made it difficult to aggregate these studies for meta-analysis; hence they were only described (see online supplementary table S3).…”
Section: Resultsmentioning
confidence: 99%
“…5 In Matthew et al, the prevalence of asthma among children aged 5-10 years was 9.5% and among children aged 11-15 years was 7.27%. 9 In Animesh Jain et al, the prevalence of asthma was significantly higher among younger age group (14.9% in 6-9 years) and decreased with increasing age. 6 It was 8.7% among 10-12 years' age group and 5.5% among 13-15 years' age group.…”
Section: Discussionmentioning
confidence: 99%
“…7 In Tamil Nadu, data from Chennai published in 2002 showed that the prevalence of diagnosed asthma was 5% in children below 12 years of age. 8 A study conducted by Matthew et al 9 in Coimbatore in 2012 showed that prevalence of asthma in 11-15 years was 7.27%. A study conducted by Kumar et al 10 in Pudhucherry in 2014 showed that prevalence of asthma in 12-16 years was 5.23%.…”
Section: Discussionmentioning
confidence: 99%